Ultrasound-assisted polysaccharide extraction from Fritillaria ussuriensis Maxim. and its structural characterization, antioxidant and immunological activity - Jiang, Shuang; Wang, Qianbo; Wang, Zhibin; Borjigin, Gilwa; Sun, Jiahui; Zhao, Yue; Li, Qi; Shi, Xuepeng; faizan ali shah, Syed; Wang, Xiaotong; Gan, Chunli; Wu, Yanli; et al. (Ultrasonics sonochemistry, 2024)
[Display omitted] Fritillaria ussuriensis Maxim. (F.M.) has been widely used in both food and medication for more than 2000 years. In order to achieve its comprehensive utilization and investigate the structural characterization and biology activity, response surface methodology (RSM) was used to optimize the ultrasound-assisted extraction conditions of F.M. polysaccharides. The optimal extraction conditions were ultrasonic power of 174.2 W, ratio of liquid to material of 40.7 mL/g and ultrasonic time of 82.0 min. In addition, a neutral polysaccharide F-1 was obtained, and its structure characterization, antioxidant and immunological activity were evaluated. The structural properties of the polysaccharide were characterized by UV, IR, GC-MS, NMR and AFM. Monosaccharide composition of F-1 (MW 18.11 kDa) was rhamnose, arabinose, glucosamine hydrochloride, galactose, and glucose which under the ratio of 0.9: 3.8: 0.2: 2.9: 92.2. The fractions of F-1 were mainly linked by → 6)-α-D-Glcp-(1 → with branch chain α-D-Glcp-(1 → 4)-α-D-Glcp-(1 → and 4,6)-α-D-Glcp-(1 → residues. Moreover, F-1 has a significant scavenging activity, which can clear hydroxyl radicals, superoxide anion, DPPH and ABTS. In addition, the immunological activity showed that F-1 had an effect on macrophage phagocytic activity. And it can increase the release of inflammatory factors including TNF-α, IL-1β and IL-6. F-1 is a novel polysaccharide with significant activity in antioxidant and immunological activity, which has great potential for antioxidant and immunizer in food, pharmaceutical and cosmetic industries. The study can provide a methodological basis for polysaccharide research and theoretical basis for the industrialized production and practical application.